An Analysis of Learning Styles and Learning Strategies Used by a Successful Language Learner - Salam, Urai; Sukarti; Arifin, Zainal (Prodi. Pendidikan Bahasa Inggris, FKIP, Universitas Kristen Indonesia, 2020)
This study aimed to describe major learning styles and learning strategies used by a research subject from four years of a college student of English Education Study Program. It was a qualitative study and conducted through a case study design. The subject was a successful four years college student. The data was collected through questionnaires, interviews, and documents. Two questionnaires were administered, Perceptual Learning Style Preferences Questionnaire (PLSPQ) to determine the student learning style preferences, whereas, Strategy Inventory for Language Learning (SILL) to determine the student learning strategies. A semi-structured interview was applied to gain the primary data, while, the document was provided to support it. The results revealed that the successful language learner performed two major learning styles proposed by Reid (1984), i.e. visual, in which the subject learns best by reading and taking notes; and the individual, in which the subject learns better individually. Subsequently, the subject uses two major learning strategies proposed by Oxford (1990). The first learning strategy is the cognitive strategy includes practicing along with receiving and sending messages. The second strategy is the compensation strategy includes guessing intelligently in listening and reading and overcoming limitations in speaking and writing.